(untitled) (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was carried out in Grey Terrace Soil of Joydebpur and Non Calcareous Grey Floodplain Soil of Agricultural Research Station, Burirhat, Rangpur during the rabi season of 2010-2011 and 2011-2012. The objectives were to evaluate the effect of boron on the yield and yield attributes of BARI Hybrid Tomato-5 as well as to determine an optimum rate of boron application for maximizing yield. Three varieties of BARI Hybrid Tomato-5 viz., Epoch, NS 815 and BARI Hybrid-5 and five levels of boron (0, 0.5, 1.0, 1.5 and 2.0 kgB ha-1) along with a blanket dose of N220 P60 K120 S40 Zn4.0 kg ha-1 and cow dung 5 t ha-1 were used in the study. Results revealed that NS 815 performed the best with 1.5 kg B ha-1 that produced 79.7 t ha-1 at Joydevpur whereas at Burirhat Epoch performed best (101 t/ha). The said combination increased 31.7% and 57.8% yield over the control at Joydevpur and Burirhat, respectively. However, from regression analysis, a positive but quadratic relationship was observed between yield and boron levels. The optimum dose of boron was appeared to be as 1.37 kg and 1.54 kg B ha-1 for Joydevpur and Burirhat, respectively. Bangladesh J. Agril. Res. 42(4): 707-714, December 2017